Compulsory Voting and Voter Turnout in the Low Countries: A Qualitative Data Analysis of the Case Vlaams Belang - Hennau, Sofie; Ackaert, Johan (Politics of the Low Countries, 2025)
In recent decades research on voter turnout has vastly increased, especially because of the structural trend towards lower turnout in western societies. Some scholars consider the introduction of a system of compulsory voting as an effective tool to counter this trend.